2018
DOI: 10.1371/journal.pone.0192593
|View full text |Cite
|
Sign up to set email alerts
|

Change in hippocampal theta oscillation associated with multiple lever presses in a bimanual two-lever choice task for robot control in rats

Abstract: Hippocampal theta oscillations have been implicated in working memory and attentional process, which might be useful for the brain-machine interface (BMI). To further elucidate the properties of the hippocampal theta oscillations that can be used in BMI, we investigated hippocampal theta oscillations during a two-lever choice task. During the task body-restrained rats were trained with a food reward to move an e-puck robot towards them by pressing the correct lever, ipsilateral to the robot several times, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Classically, theta oscillations in the rat hippocampus have been associated with preparatory movements and locomotor behavior ( Vanderwolf and Heron, 1964 ). Many previous studies have reported that theta oscillations strongly correlate with locomotion speed ( Vanderwolf, 1969 , 1971 ; McFarland et al, 1975 ; Sławińska and Kasicki, 1998 ; Buzsáki, 2005 ; Hinman et al, 2011 ; Long et al, 2014 ), while others have suggested that theta oscillations are not purely associated to locomotion speed but better reflect movement intensity in general ( Whishaw and Vanderwolf, 1973 ; Bland et al, 2006 ; Tanaka et al, 2018 ). Since treadmill speed was always the same in our experiment (30 cm/s), according to the locomotion speed/movement intensity hypothesis, one would expect no changes in theta power across subsequent runs.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, theta oscillations in the rat hippocampus have been associated with preparatory movements and locomotor behavior ( Vanderwolf and Heron, 1964 ). Many previous studies have reported that theta oscillations strongly correlate with locomotion speed ( Vanderwolf, 1969 , 1971 ; McFarland et al, 1975 ; Sławińska and Kasicki, 1998 ; Buzsáki, 2005 ; Hinman et al, 2011 ; Long et al, 2014 ), while others have suggested that theta oscillations are not purely associated to locomotion speed but better reflect movement intensity in general ( Whishaw and Vanderwolf, 1973 ; Bland et al, 2006 ; Tanaka et al, 2018 ). Since treadmill speed was always the same in our experiment (30 cm/s), according to the locomotion speed/movement intensity hypothesis, one would expect no changes in theta power across subsequent runs.…”
Section: Discussionmentioning
confidence: 99%